Correction: Dual Energy X-Ray Absorptiometry Compared with Anthropometry in Relation to Cardio-Metabolic Risk Factors in a Young Adult Population: Is the 'Gold Standard' Tarnished? - Denise L Demmer; Lawrence J Beilin; Beth Hands; Sally Burrows; Kay L Cox; Craig E Pennell; Stephen J Lye; Jennifer A Mountain; Trevor A Mori (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0162164.].